The Socialization of Managing Avocado Seeds into Healthy Tea is a Business Ideas to Overcome Extreme Poverty - Nasution, Auliya Shalha; Ayu S, Hanifa; Saragih, Muhammad Darul Aswad; Pira Azara; Syahinda, T. Razita; Yenni Samri Juliati Nasution (Society : Jurnal Pengabdian Masyarakat, 2026)
The  In Namu Ukur Village, the Community Service Program (KKN) was implemented to educate and teach the locals on how to use avocado seeds as a profitable and healthful tea product. The village's high level of extreme poverty and the amount of wasted avocado seeds served as the impetus for this socialization activity, which calls for straightforward, affordable, and basic business solutions. The initiative included processing demonstrations, awareness seminars, and hands-on support for local adolescents and groups of women. The findings demonstrated that the community could comprehend the cleaning, drying, roasting, and product packaging steps involved in turning avocado seeds into herbal tea. In addition to its health benefits, avocado seed tea has a promising economic future due to its inexpensive manufacturing costs and easily accessible raw materials. Through this program, the residents of Namu Ukur Village learned how to create business concepts based on local resources that may be used as an alternate strategy to boost the local economy and combat extreme poverty.